Depictions of board games in petroglyphs - Damchaabadgar, Sodnomjamts (Studia Archaeologica, 2022)
In this article, the representations of board games in the rock paintings found in Mongolia area compared with the findings from other places, and to offer some suggestions are made about the purpose and related chronology. Among them, the depictions in the petroglyphs of Khoroon Oroi mountain in Davst sum, Uvs province, are similar to the board games called “jirgee” related to the Uyghur period, while the depictions in Tevsh mountain in Bogd sum, Uvurkhangai province, Tehtien Khutel in Davst sum, Uvs province, and Buvuu rock paintings in Zavkhan sum, are similar to the Liao period tomb and It is similar to a board game called a “buga” found in the medieval city of Kharkhorum. At present, in the Mongolian territory, in the Xiongnu, Turkic, Uyghur, Khitan and Mongolian empires, many board games and piece have been found and there are also many evidences of these being carved into rock paintings for the purpose of playing games or some kind of symbol. The above facts are an important tool to show the extent of the intellectual culture of the ancient nomads who lived in Mongolia, and it also shows that we Mongolians are a people with a centuries old rich tradition of board games. Хадны зураг дахь хөлөгт тоглоомын дүрслэлүүд Товчлол. Энэхүү өгүүлэлд Монгол нутгаас илэрч олдсон хадны зураг дахь хөлөгт тоглоомын дүрслэлүүдийг бусад газрын биед олдворуудтай харьцуулан үзэж зургийн утга агуулга, холбогдох он цагийн талаар зарим саналыг дэвшүүлжээ. Эдгээрийн дотроос Увс аймгийн Давст сумын Хороон орой уулын хадны зураг дахь дүрслэл нь Уйгурын үед холбогдох жиргээ хэмээх хөлөгт тоглоомуудтай ижилсэж байгаа бол Өвөрхангай аймгийн Богд сумын Тэвш уул, Увс аймгийн Давст сумын Тэхтийн хөтөл, Завхан сумын Бувуугийн хадны зураг дахь дүрслэлүүд Ляо улсын үеийн бунхан болон дундад зууны үеийн Хархорум хотоос олдсон буга хэмээх хөлөгт тоглоомтой төстэй байна. Одоогийн байдлаар монгол нутгаас НТӨ I зуунаас НТ XIV зуун хүртлэх хугацаанд хамаарах олон тооны хөлөгт тоглоомын олдворууд илэрч олдсоноос гадна хадны зурагт бас сийлж үлдээсэн хэд хэдэн шинэ баримт байна. Түлхүүр үгс: Хадны зураг, Уйгурын хаант улс, хөлөгт тоглоом, жиргээ, уулын буга